Molecular and cellular biophysics - Tuszynski, J. A. (Chapman & Hall/CRC, 2008)
Tuszynski introduces undergraduate students in the biological sciences to the application of concepts and techniques from physics in the study of biological systems, focusing here on the smallest units. He covers what life is, the molecules of life, biological cells, and life processes. Chapter-end problems are included, as is a glossary without pronunciation indicated.